(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: In Bangladesh, 25/1000 cases of neonates are born with mild to severe type of congenital heart disease. Significant numbers of cases from new born to adult age group are reporting to OPD clinics with broad spectrum of congenital and grown up untreated heart diseases. This study will cover pattern of diseases among cases selected for cardiac catheterization and intervention in study group in a cardiac hospital with limited facility for children. Objectives: To analyze all the cases who had cardiac catheterization and intervention in said period and to see the outcome. Materials and Methods: It is a retrospective study conducted in a cardiac hospital from December 2014 to December 2019. All cases of cardiac catheterization and interventions were included in the study. Pattern of diseases, interventions, management and outcomes were analyzed. Results: Out of 1179 cases, 44.87% were male and 55.13% were female. Two hundred fifty four cases(21.54%) were in 0-1 year age group, 44.02% were in >01-05 year age group, 18.66% cases were in > 5 to 10 year , 8.48% cases were in >10 to 20 years, 4.83% cases were in> 20 to 30 years and 2.46% cases were in more than 30 year age group. Among trans-catheter closure patent ductus arteriosus (PDA) was the commonest type of intervention (44.68%), followed by atrial septal defect (ASD) (25.20%), ventricular septal defect (VSD) (11.83%) and balloon valvoplasty (BVP) for pulmonary stenosis (11.63%). Neonatal interventions were minimum as the coronary care unit used as post cathward had limited facility for neonatal care. PDA stenting was performed in 0.81% cases and BAS in 0.91% cases. Many patients underwent more than one intervention at a time; most common was ASD device closure and pulmonary valvoplasty. Cardiac Catheterization studies were minimum in this series and most of the cath study cases were VSD or/with other combinations (4.48%). Among infants (254), PDA device closure was the commonest intervention (64.56%) followed balloon valvoplasty for PS (15.35%) and balloon dilation of Coarctation on aorta (7.87%). Among implants, most commonly used were 8/6 mm (14.59%) Amplatzer Duct occluder (ADO), 6/4 ADOII, MF-Konar (9.79%) device and most common balloon used for valve or vessel dilation was 10x3 mm Tyshak II (3.26%). Only one mortality was noticed in a case of double intervention of critical Aortic and pulmonary valve stenosis. Conclusion: Commonest and established interventions were performed in this study other than few life saving interventions in neonates and outcome was excellent. Skilled team of pediatric cardiologist and technician in catheterization laboratory can bring success at the end of the day in spite of challenges. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 3-9